Isolation of toxoplasma gondii from goats from Brazil - Ragozo, A. M A; Yai, L. E O; Oliveira, L. N.; Dias, R. A.; Gonçalves, H. C. [UNESP]; Azevedo, S. S.; Dubey, J. P.; Gennari, S. M. (American Society of Parasitologists, 2009)
Goats are economically important in many countries, and little is known of caprine toxoplasmosis in Brazil. Antibodies to Toxoplasma gondii were assayed in the sera of 143 goats from 3 Brazilian states, using modified agglutination test (MAT titer ≥1:25); 46 (32.2%) tested positive. Samples of brain, heart, diaphragm, and masseter of seropositive animals were pooled, digested in pepsin, and bioassayed in mice. Viable T. gondii specimens were isolated from tissue homogenates of 12 goats; the isolates were designated TgGtBr1-12. Ten of the 12 isolates killed 100 of infected mice, indicating that goats can harbor mouse-virulent T. gondii and, hence, can serve as a source of infection for humans. © 2009 American Society of Parasitologists.
Keywords: antibody; bioassay; brain; goat; health risk; intermediate host; meat; parasite; protozoan; public health; virulence; animal experiment; animal tissue; Brazil; female; male; mouse; nonhuman; parasite isolation; seroprevalence; Toxoplasma gondii; Animalia; Capra; Capra hircus; Mus